Electrochemical techniques applied to the study of archaeological pigments. The Voltammetry of Microparticles - Paez, Maria Cecilia (2014)
The Voltammetry of Microparticles (VMP) is an analytical technique mainly applied to the industrial field. The present work explores its utility in Archaeology, through the identification of the mineral composition of paints and engobes used in the c oating of archaeological ceramic pieces. Its application enabled the detection of the use of mineral composites such as magnetite and hematite in the obtention of black and red pigments